Akselerasi Daya Saing UMKM Kuliner PKK melalui Digital Marketing dan Pembayaran Non Tunai - Muhammad Virza Dwiriandry; Fuji Kartika Sari; Siti Istiqomah; Muhammad Agratha Friezsanda (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Micro, small, and medium enterprises (MSMEs) play a strategic role in strengthening the local economy; however, many women-led culinary MSMEs affiliated with the Family Welfare Movement (PKK) in Kelapa Indah Village, Tangerang City, still rely on conventional marketing and cash-based transactions. These limitations reduce market reach, operational efficiency, and business competitiveness. Therefore, this community service program aimed to enhance participants' knowledge and practical skills in digital marketing and cashless payment systems to support sustainable business development. The program was conducted on June 7, 2026, at the Kelapa Indah Village Hall, Tangerang City, involving 25 active culinary MSME owners from the PKK community. The implementation adopted a solution-oriented training approach through an interactive seminar, group discussions, case-based learning, and hands-on practice. The activities were carried out by a team consisting of one lecturer from the Master of Management Program, Universitas Pamulang, and four undergraduate student assistants. Training materials covered Business Model Canvas (BMC), product photography, persuasive copywriting, social media marketing, and the implementation of QRIS and electronic wallet payment systems. The results indicated a qualitative improvement in participants' understanding and practical competencies in digital promotion and digital financial management. Participants demonstrated high engagement throughout the program, reflected in active discussions and increased confidence in applying digital marketing strategies and cashless payment technologies. These findings suggest that integrating digital marketing literacy with digital financial practices can strengthen technology adoption and improve the long-term competitiveness of community-based culinary MSMEs.